PERANCANGAN ESCAPE HEALING PADA GEDUNG NITOUR DI KAWASAN HARMONI SEBAGAI THIRD PLACE DENGAN PENDEKATAN INFILL - Theana, Biancha; Solikhah, Nafiah (Jurusan Arsitektur dan Perencanaan, 2025)
One of the icons in the Harmoni area of Central Jakarta is the Nitour Building, which was originally known as the Oger Freres Building in 1810. It served as a tailor shop for glamorous Dutch women's attire before parties at the Societeit De Harmonie building. The strength of Harmoni’s sense of place at that time lay in its role as the center of social and cultural activity in Batavia. The name